1998
DOI: 10.1053/euhj.1997.0731
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinaemia, regional adipose tissue distribution and left ventricular mass in normotensive, elderly, obese subjects

Abstract: Obesity is a metabolic condition, related to abnormalities of the glyco-insulinaemic metabolism, and plays a substantial role in the development of cardiovascular disease. The aim of this study was to establish a correlation among left ventricular mass, evaluated echocardiographically according to Penn Convention criteria, blood pressure, evaluated by ambulatory blood pressure monitoring, anthropometric indices for evaluation of body mass index and waist to hip ratio circumference, regional adipose tissue dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 43 publications
(50 reference statements)
4
28
0
1
Order By: Relevance
“…A potential limitation of the present study is that the insulin levels were assessed in the fasting state but not in response to glucose loading. Several studies have found a positive association between postload insulin levels or area under the postload insulin curve and LV structural variables (22)(23)(24). In a recent investigation, the HOMA value was related to LV mass in women alone, but this relation was largely accounted for by obesity (9).…”
Section: Discussionmentioning
confidence: 94%
“…A potential limitation of the present study is that the insulin levels were assessed in the fasting state but not in response to glucose loading. Several studies have found a positive association between postload insulin levels or area under the postload insulin curve and LV structural variables (22)(23)(24). In a recent investigation, the HOMA value was related to LV mass in women alone, but this relation was largely accounted for by obesity (9).…”
Section: Discussionmentioning
confidence: 94%
“…In adults, previous studies reported that VAT was correlated with LVM and LV internal dimension during diastole. 24,25 Cardiovascular involvement (ie, hypertension, increased LVM, cardiac malfunction) can be identified in early stages of obesity. Possible rationales may include volume overload or humoral activation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these studies reported that the significance of a relation between LVM and insulin sensitivity disappeared after body mass or size was adjusted for, suggesting that insulin or insulin sensitivity was a covariate to body mass or size rather than LVM. 12,16,[18][19][20][21] In fact, few studies have even reported that obesity is related to LVM, independent of high BP. [22][23][24] In a substudy to the Captopril Prevention Project (CAPPP), 20 there were no significant relations between LVM, LVM index, and insulin levels, insulin sensitivity (assessed by euglycaemic insulin clamp) or insulin turnover in 51 previously untreated middle-aged nondiabetic hypertensive patients.…”
mentioning
confidence: 99%
“…18 Furthermore, another study in normotensive elderly patients (mean age 68 years) has also indicated a strong relation (independent of BP values) between LVMHt 2.7 and insulin sensitivity in obese subjects (especially in those with centripetal adipose tissue distribution), but not in lean normotensive subjects. 19 Thus, obesity appears to play a central role in these interactions. Indeed, in a cohort of 322 healthy, normotensive junior high school aged children undergoing euglycaemic insulin clamp procedures, LVM was not related to insulin resistance, fasting insulin, BP, or lipid levels when the correlations were adjusted for adiposity.…”
mentioning
confidence: 99%